Hip Muscle Forces and Contact Loading During Squatting After Cam-Type FAI Surgery. (4th November 2020) - Catelli, Danilo S.; Ng, K.C. Geoffrey; Wesseling, Mariska; Kowalski, Erik; Jonkers, Ilse; Beaulé, Paul E.; Lamontagne, Mario
Abstract : Background: The purpose of this study was to compare muscle forces and hip contact forces (HCFs) during squatting in patients with cam-type femoroacetabular impingement (cam-FAI) before and after hip corrective surgery and with healthy control participants. Methods: Ten symptomatic male patients with cam-FAI performed deep squatting preoperatively and at 2 years postoperatively. Patients were matched by age and body mass index to 10 male control participants. Full-body kinematics and kinetics were computed, and muscle forces and HCFs were estimated using a musculoskeletal model and static optimization. Normalized squat cycle (%SC ) trials were compared using statistical nonparametric mapping (SnPM). Results: Postoperatively, patients with cam-FAI squatted down with higher anterior pelvic tilt, higher hip flexion, and greater hip extension moments than preoperatively. Preoperative patients demonstrated lower anterior pelvic tilt and lower hip flexion compared with the participants in the control group. Postoperative patients showed increased semimembranosus force compared with their preoperative values. Preoperative forces were lower than the control group for the adductor magnus, the psoas major, and the semimembranosus; however, the preoperative patients showed greater inferior gluteus maximus forces than the patients in the control group, whereas the postoperative patients did not differ from the control patients. Higher posterior, superior, and resultant HCF magnitudes were identified postoperatively in comparison with the preoperative values. Preoperative posterior HCF was lower than in the control group, whereas the postoperative posterior HCF did not differ from those in the control group. Conclusions: Higher postoperative anterior pelvic tilt was associated with an indication of return to closer to normal pelvic motion, which resembled data from the control group. Lower preoperative anterior pelvic tilt was associated with muscle force imbalance, indicated by decreased semimembranosus and increased gluteus maximus forces. The overall increased postoperative muscle forces were associated with improved pelvic mobility and increased HCFs that were comparable with the control-group standards. Clinical Relevance: Muscle forces and HCFs may be indicative of postoperative joint health restoration and alleviated symptoms.